A formação docente na constituição de micropolíticas ativas como possibilidade de resistir, dobrar e inventar - Vacileski, Sunamita Astir Daud de Souza (2023)
This dissertation moves through training and curricular territories among possibilities of resisting, bending and inventing. The route constitutes the “between” place of two cartographic movements: training with teachers in the areas of History and Geography in dialogue with the Municipal Department of Education of Serra-ES and training with teachers and other education professionals at a school in that municipality. It aims to map, in these spaces of continued training, active micropolitical movements that resist the mechanisms of hegemonization of education and enhance inventive curricula, forged in the daily lives of schools. As theoretical Intercessors, teachers, Carvalho, Deleuze and Guattari, Dias, Kastrup and Rolnik, participate in this research with the intention of affirming other possibilities for curricula and teacher training. It uses rhizomatic cartography as a methodological approach, making it possible to wander and fly on witches' brooms in the desire to escape the border lines of sedentary spaces. It is understood that mapping is following processes in the encounter with others, with ideas, thoughts, events and everything that moves the research territory, causing other possibilities to proliferate. It defends other ways of thinking, practicing curricula and teacher training in a field of possibilities, invention and resistance that escape the determinisms and fatalisms of established educational policies that are configured by a neoliberal order. Bet, with teachers, on the inventive movements that inhabit school daily life as an opening to other worlds and existences that conspire-breathe life through perspectives outside the obvious of a representational cognitive system.